Spatio-temporal dynamism of hotspots enhances plant diversity (2009)
Dispersal and in situ speciation are seen as the main mechanisms behind the accumulation of species in an area. Biodiversity hotspots are often composed of a particular vegetation type that occupies a discrete geographical area. Recent studies focusing on these hotspots have demonstrated the contribution of ex situ speciation to their diversity. A proportion of the extant endemics that are found in hotspots originated outside the present-day boundaries of hotspots. It is possible that historically the vegetation type that the hotspot currently occupies may have previously had a larger distribution. Geologically or climatically induced repeated fragmentation followed by re-expansion of the range of this vegetation may have acted as a species pump that may in part explain the high species diversity of hotspots. This idea is similar to that of the expansion and contraction of ranges during the Pleistocene being a causal factor in generating species diversity. However, dated molecular phylogenies indicate that much of the speciation in hotspots did not occur during the Pleistocene but instead occurred during the Tertiary. Expansion and contraction of vegetation types could, however, have taken place over greater periods of time than encompassed by the Quaternary, and we highlight examples of these here and emphasize a role for vicariance in the generation of diversity